Suprapubic Aspiration under Ultrasound Guidance (Educational Video) - Hassanzadeh Rad, Afagh; Badeli, Hamidreza; Jamshidi, Sahab (Journal of Pediatric Nephrology, 2019)
Urinary Tract Infections (UTIs) are common diseases during infancy. Urine exam and urine culture are definite diagnostic methods. Based on the latest American Academy of Pediatrics guideline, Catheterization or Suprapubic aspiration (SPA) are the methods of choice for urine culture and analysis.